IWV / MFI cocrystallization molecular sieve and preparation method and application thereof
Synthesis of IWV/MFI co-crystalline molecular sieve containing silicon, germanium and trivalent backbone elements by a single template agent method, solving the problem of expensive template agents and toxic gases in the preparation of IWV molecular sieve, and achieving efficient preparation and excellent co-crystalline molecular sieve Catalytic performance meets different catalytic reaction needs.
Patent Information
- Application Number
- CN202310805855.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-03
AI Technical Summary
The template agent used in the existing preparation methods of IWV molecular sieve is expensive and produces toxic gases when calcined at high temperatures. There are few studies on IWV/MFI co-crystallized molecular sieves, and there is a lack of adjustable two-phase ratio synthesis methods.
The IWV/MFI co-crystalline molecular sieve containing silicon, germanium and trivalent backbone elements was synthesized by a single template agent method. By adjusting the molar ratio of SiO2 to GeO2 and the ratio of trivalent elements, the preparation of co-crystalline molecular sieve is achieved. The process is simple and the cost is low. and increase catalytic active sites by substitution of non-silicon tetravalent elements.
It realizes the efficient preparation of IWV/MFI co-crystalline molecular sieve, has excellent adsorption and catalytic properties, can meet the needs of different catalytic reactions, and reduces the preparation cost.
Smart Images

Figure BDA0004317738770000021 
Figure BDA0004317738770000031 
Figure BDA0004317738770000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of porous materials, and in particular relates to an IWV / MFI co-crystallized molecular sieve and a preparation method and application thereof. Background Art
[0002] Co-crystallized molecular sieves refer to co-crystallizations formed by two or more molecular sieves, or composite crystals with structural characteristics of two or more molecular sieves. Such molecular sieves often have properties different from those of a single molecular sieve or a corresponding mechanical mixture. Since co-crystal molecular sieves have multiple structures and superposition functions, they avoid the defects of a single pore structure system, have great advantages in molecular adsorption and diffusion, and have broad application prospects in the field of oil refining catalysis. Common co-crystallized molecular sieves include ZSM-5 / ZSM-11 (CN 1137022A), MCM-49 / ZSM-35 (Micropro. Mesopro. Mater., 2009, 121, 166-172), BEA / MOR (Chin. J Catal., 2006, 27: 228-232), etc.
[0003] IWV molecular sieve is a macroporous molecular sieve. Its framework consists of two intersecting pore systems with openings of 2.1×10-1.3×10-1 in the
[001] and
[011] directions. 12-membered ring channel. The framework elements of IWV molecular sieve are generally silicon aluminum, with acidic active centers, and can be used for acid catalytic reactions. Researchers from the Polytechnic University of Valencia, Spain, first disclosed the structure and preparation method of IWV molecular sieve in patent WO2006055305A2. The template used in the synthesis is diphenyldimethylphosphonium hydroxide. The main problem of this synthesis method is that the template is expensive and produces toxic PH3 gas during high-temperature roasting. MFI molecular sieve (US 3,702,886) is a medium-pore molecular sieve. Its framework consists of two intersecting channel systems, in which the opening diameter of the straight cylindrical channel in the
[010] direction is 0.53×0.56nm; the opening diameter of the "Z"-shaped channel in the
[100] direction is 0.51×0.55nm. MFI molecular sieve is widely used in catalytic cracking to increase propylene production and improve gasoline octane number, toluene disproportionation, olefin cracking, benzene alkylation and other catalytic processes.
[0004] Currently, there are few reports on IWV / MFI co-crystal molecular sieves. In order to enrich the types of molecular sieves, it is very important to use a single template method to synthesize IWV / MFI co-crystal molecular sieves with adjustable two-phase ratios. Summary of the invention
[0005] The purpose of the present invention is to provide an IWV / MFI co-crystallized molecular sieve and its preparation method and application. The IWV / MFI co-crystallized molecular sieve of the present invention contains silicon, germanium and trivalent skeleton elements, uses multiple skeleton elements, increases catalytic active sites, and has excellent adsorption and catalytic performance. The present invention can realize the preparation of IWV / MFI co-crystallized molecular sieve using a single template, and the ratio of the two phases in the co-crystallization is adjustable, the process is simple, and the cost is low.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In the first aspect, the present invention provides an IWV / MFI co-crystallized molecular sieve, the chemical composition of which is "m SiO2·nGeO2·x XO 1.5 ", where X is a skeleton trivalent element, the molar ratio of SiO2 to GeO2 is m:n = (2.5-10): 1, and the sum of the molar numbers of SiO2 and GeO2 is equal to XO 1.5 The molar ratio (m+n): x=(35-80):1.
[0008] In the co-crystallized molecular sieve of the present invention, the molar ratio m / n of SiO2 to GeO2 can be 2.5:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value therebetween, preferably 3≤m / n≤8.
[0009] In the co-crystallized molecular sieve of the present invention, the sum of the molar numbers of SiO2 and GeO2 is equal to the molar number of the XO 1.5 The molar ratio (m+n) / x can be 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1, 70:1, 75:1, 80:1 or any value therebetween, preferably 40≤(m+n) / x≤60.
[0010] In some embodiments, in the IWV / MFI co-crystallized molecular sieve, the sum of the molar numbers of SiO2 and GeO2 is 1, that is, m+n=1.
[0011] In some embodiments, X is selected from at least one of Group IIIA elements, Group VIII elements, Group VIB elements, or Group IIIB elements, preferably at least one of aluminum, boron, iron, gallium, indium, and chromium, and more preferably at least one of aluminum and boron.
[0012] The Si in the IWV / MFI co-crystallized molecular sieve of the present invention can also be replaced by at least one non-silicon tetravalent framework element Y. In some embodiments, the non-silicon tetravalent framework element Y is selected from tin, titanium, zirconium and hafnium. In some embodiments, no more than 10wt% of the Si element in the molecular sieve is replaced by at least one non-silicon tetravalent framework element Y. In some embodiments, 1-9wt% of the Si element in the molecular sieve is replaced by at least one non-silicon tetravalent framework element Y.
[0013] The present invention partially replaces the Si element in the IWV / MFI co-crystallized molecular sieve framework with a non-silicon tetravalent element Y, and then introduces one or more other elements into the framework to generate different catalytic active centers to meet the needs of different catalytic reactions.
[0014] In some embodiments, the X-ray diffraction pattern of the IWV / MFI co-crystallized molecular sieve includes characteristic peaks as shown in Table 1 below:
[0015] Table 1
[0016]
[0017]
[0018] In the present invention, in the X-ray diffraction pattern, vw, w, m, s, and vs represent the diffraction peak intensity, vw means very weak, w means weak, m means medium, s means strong, and vs means very strong; generally speaking, vw means less than 5%, w means 5%-20%, m means 20%-40% (including 20% and 40%), s means 40%-70%, and vs means greater than 70% (including 70%).
[0019] Since the strength is affected by many factors, the data in Table 1 are expressed as the interplanar spacing of the IWV / MFI co-crystallized molecular sieve at 2θ(°) of 7.84±0.2. It is 11.27±0.55, and so on. The representation method of this table is well known to those skilled in the art, and the present invention will not explain them one by one here.
[0020] The co-crystallized molecular sieve of the present invention has two physical phases of IWV molecular sieve and MFI molecular sieve. In some embodiments, in the IWV / MFI co-crystallized molecular sieve, the weight percentage of IWV molecular sieve is 1%-99%, preferably 5%-95%. In some embodiments, in the IWV / MFI co-crystallized molecular sieve, the weight percentage of MFI molecular sieve is 1%-99%, preferably 5%-95%. In the co-crystallized molecular sieve of the present invention, the weight percentage of the IWV molecular sieve and the MFI molecular sieve in the co-crystallized molecular sieve is adjustable within the range of 1% to 99%.
[0021] In the present invention, the weight percentage of IWV molecular sieve and MFI molecular sieve in the IWV / MFI co-crystallized molecular sieve is obtained by measuring the relative proportion of the sum of their characteristic diffraction peak areas to the sum of the characteristic diffraction peak areas of IWV and MFI molecular sieves.
[0022] In some embodiments, in the IWV / MFI co-crystallized molecular sieve, the IWV molecular sieve is in the form of a sheet. In some embodiments, in the IWV / MFI co-crystallized molecular sieve, the MFI molecular sieve is in the form of a block. In some embodiments, the IWV / MFI co-crystallized molecular sieve comprises a sheet-like IWV molecular sieve and a block-like MFI molecular sieve.
[0023] In a second aspect, the present invention provides a method for preparing the IWV / MFI co-crystallized molecular sieve according to the first aspect, comprising the following steps:
[0024] A mixed solution containing a silicon source, a germanium source, an optional non-silicon tetravalent framework element Y source, a trivalent framework element X source, a fluorine source, a structure directing agent R and water is subjected to a crystallization reaction to obtain an IWV / MFI co-crystallized molecular sieve.
[0025] The present invention does not specifically limit the preparation method of the mixed solution. For example, a germanium source, an optional non-silicon tetravalent skeleton element Y source, and a trivalent skeleton element X source may be mixed first, and then a silicon source, a fluorine source, and water may be added in sequence to obtain the mixed solution.
[0026] In the above preparation method of the present invention, the molar number of the silicon source is calculated as SiO2, the molar number of the germanium source is calculated as GeO2, the molar number of the non-silicon tetravalent skeleton element Y source is calculated as the corresponding oxide YO2, the molar number of the trivalent skeleton element X source is calculated as X2O3, and the molar number of the fluorine source is calculated as F.
[0027] In some embodiments, in the mixed solution, the molar ratio of SiO2 to GeO2 is (2.5-10):1, for example, 2.5:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value therebetween, preferably (3-8):1.
[0028] In some embodiments, in the mixed solution, the sum of the molar numbers of SiO2 and GeO2 is 1.
[0029] In some embodiments, in the mixed solution, the molar ratio of YO2 to SiO2 is (0-0.1):1, such as 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1 or any value therebetween. In some embodiments, in the mixed solution, the molar ratio of YO2 to SiO2 is (0.01-0.09):1. In some embodiments, in the mixed solution, the molar ratio of YO2 to SiO2 is (0.01-0.05):1.
[0030] In some embodiments, in the mixed solution, the ratio of the sum of the molar numbers of SiO2 and GeO2 to the molar number of X2O3 is (70-160):1, for example 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 30:1, 140:1, 150:1, 160:1 or any value therebetween, preferably (80-120:1).
[0031] In some embodiments, in the mixed solution, the ratio of the sum of the molar numbers of SiO2, GeO2 and YO2 to the molar number of X2O3 is (70-160):1, for example 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 30:1, 140:1, 150:1, 160:1 or any value therebetween, preferably (80-120:1).
[0032] In some embodiments, in the mixed solution, the molar ratio of the sum of the molar numbers of SiO2 and GeO2 to F is 1:(0.2-4), for example, 1:0.2, 1:0.3, 1:0.35, 1:0.5, 1:0.8, 1:1.0, 1:1.2, 1:1.5, 1:2, 1:2.5, 1:2.8, 1:3, 1:3.5, 1:4 or any value therebetween, preferably 1:(0.35-2.5).
[0033] In some embodiments, the ratio of the sum of the molar numbers of SiO2, GeO2 and YO2 to the molar number of F is 1:(0.2-4), for example, 1:0.2, 1:0.3, 1:0.35, 1:0.5, 1:0.8, 1:1.0, 1:1.2, 1:1.5, 1:2, 1:2.5, 1:2.8, 1:3, 1:3.5, 1:4 or any value therebetween, preferably 1:(0.35-2.5).
[0034] In some embodiments, in the mixed solution, the molar ratio of the sum of the molar numbers of SiO2 and GeO2 to the structure directing agent R is 1:(0.15-4), for example, 1:0.15, 1:0.2, 1:0.35, 1:0.5, 1:1.0, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4 or any value therebetween, preferably 1:(0.35-2).
[0035] In some embodiments, in the mixed solution, the molar ratio of the sum of the molar numbers of SiO2, GeO2 and YO2 to the structure directing agent R is 1:(0.15-4), for example, 1:0.15, 1:0.2, 1:0.35, 1:0.5, 1:1.0, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4 or any value therebetween, preferably 1:(0.35-2).
[0036] In some embodiments, in the mixed solution, the ratio of the sum of the molar numbers of SiO2 and GeO2 to the molar number of water is 1:(12-40), for example, 1:12, 1:15, 1:18, 1:20, 1:22, 1:25, 1:28, 1:30, 1:32, 1:35, 1:38, 1:40 or any value therebetween, preferably 1:(15-30).
[0037] In some embodiments, in the mixed solution, the ratio of the sum of the molar numbers of SiO2, GeO2 and YO2 to the molar number of water is 1:(12-40), for example, 1:12, 1:15, 1:18, 1:20, 1:22, 1:25, 1:28, 1:30, 1:32, 1:35, 1:38, 1:40 or any value therebetween, preferably 1:(15-30).
[0038] In some preferred embodiments, in the mixed solution, the molar ratio of structure directing agent R, SiO2, GeO2, X2O3, F and water is (0.15-4):(0.714-0.909):(0.091-0.286):(0.00625-0.0143):(0.2-4):(12-40).
[0039] In some more preferred embodiments, in the mixed solution, the molar ratio of structure directing agent R, SiO2, GeO2, X2O3, F and water is (0.35-2):(0.75-0.889):(0.111-0.25):(0.00833-0.0125):(0.35-2.5):(15-30).
[0040] The present invention can obtain co-crystallized molecular sieves with different ratios of IWV and MFI phases by adjusting the molar ratio of structure directing agent R, silicon source, germanium source, trivalent skeleton element X source, fluorine source and water in the mixed solution, and can meet different usage requirements in terms of catalysis, adsorption and the like.
[0041] In some embodiments, the silicon source is at least one selected from the group consisting of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieves, and tetraalkoxysilane.
[0042] In some embodiments, the germanium source is selected from at least one of germanium oxide, germanium nitrate, and tetraalkoxygermanium.
[0043] In some embodiments, the non-silicon tetravalent skeleton element Y source is selected from at least one of a tin source, a titanium source, a zirconium source, and a hafnium source. In the present invention, the tin source, the titanium source, the zirconium source, and the hafnium source can be conventional tin-containing compounds, titanium-containing compounds, zirconium-containing compounds, or hafnium-containing compounds in the art, respectively.
[0044] In some preferred embodiments, the tin source is selected from at least one of tin tetrachloride, stannous chloride, alkyl tin, alkoxy tin and organic tin esters. In some preferred embodiments, the titanium source is selected from at least one of tetraalkyl titanates (e.g., tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetra-n-butyl titanate), titanium tetrachloride, hexafluorotitanic acid, titanium sulfate and their hydrolyzates. In some preferred embodiments, the zirconium source is selected from at least one of zirconium nitrate, zirconium tetrachloride, zirconium oxide and alkoxy zirconium. In some preferred embodiments, the hafnium source is selected from at least one of hafnium oxide and hafnium sulfate.
[0045] Preferably, the trivalent skeleton element X source is selected from at least one of an aluminum source, a boron source, an iron source, a gallium source, an indium source and a chromium source. In the present invention, the aluminum source, the boron source, the iron source, the gallium source, the indium source and the chromium source can be conventional aluminum-containing compounds, boron-containing compounds, iron-containing compounds, gallium-containing compounds, indium-containing compounds or chromium-containing compounds in the art.
[0046] In some preferred embodiments, the aluminum source is selected from at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum chloride, pseudo-boehmite, aluminum oxide, aluminum hydroxide, silica-aluminum zeolite molecular sieve, aluminum carbonate, elemental aluminum, aluminum isopropoxide and aluminum acetate. In some preferred embodiments, the boron source is selected from at least one of boric acid, sodium tetraborate, amorphous boron oxide, potassium borate, sodium metaborate, ammonium tetraborate and organic boron esters. In some preferred embodiments, the iron source is selected from at least one of ferric sulfate, ferric nitrate, iron halide (such as ferric chloride), ferrocene and ferric citrate. In some preferred embodiments, the gallium source is selected from at least one of gallium oxide and gallium nitrate. In some preferred embodiments, the indium source is selected from at least one of indium oxide and indium nitrate. In some preferred embodiments, the chromium source is selected from at least one of chromium oxide, chromium chloride and chromium nitrate.
[0047] In some embodiments, the fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride, preferably at least one of hydrofluoric acid and ammonium fluoride.
[0048] In some embodiments, the structure directing agent R is selected from a compound containing a 1,1,3,5-tetraalkylpiperidinium ion or a compound having a structure shown in Formula I,
[0049]
[0050] In Formula I, R1 to R4 are each independently selected from H and C 1-6 The alkyl group is preferably hydrogen, methyl, ethyl, propyl, isopropyl, butyl, isobutyl and tert-butyl.
[0051] In some embodiments, the anion X in the structure directing agent - Selected from halogen ions and hydroxide ions, preferably Cl - Br - ,I - and OH - , more preferably OH - .
[0052] In some preferred embodiments, the structure directing agent R is 1,1,3,5-tetramethylpiperidinium hydroxide (1,1,3,5-TMPOH).
[0053] In some embodiments, the temperature of the crystallization reaction is 100-200°C, preferably 110-190°C, and more preferably 155-175°C.
[0054] In some embodiments, the crystallization reaction time is 72-600 hours, preferably 96-480 hours, and more preferably 120-360 hours.
[0055] The crystallization reaction described in the present invention can be carried out under dynamic or static conditions. In the present invention, the results of static or dynamic crystallization are basically the same, so the embodiments of the present invention do not specifically describe static or dynamic.
[0056] In the preparation method of the co-crystallized molecular sieve of the present invention, after the crystallization step is completed, the co-crystallized molecular sieve can also be separated from the obtained reaction mixture as a product by any conventionally known separation method, thereby obtaining the IWV / MFI co-crystallized molecular sieve of the present invention. As the separation method, for example, filtering, washing and drying the obtained reaction mixture can be cited. The filtration, washing and drying can be carried out in any conventional manner known in the art. For example, as the filtration, for example, the obtained reaction mixture can be simply filtered. As the washing, for example, washing with deionized water can be cited. As the drying temperature, for example, 40-250°C, preferably 60-150°C, can be cited, as the drying time, for example, 8-30 hours, preferably 10-20 hours can be cited. The drying can be carried out at normal pressure or under reduced pressure.
[0057] In the preparation method of the co-crystallized molecular sieve of the present invention, the co-crystallized molecular sieve obtained according to the preparation method of the co-crystallized molecular sieve can also be calcined as needed to remove the organic template and possible moisture, etc., thereby obtaining the calcined IWV / MFI co-crystallized molecular sieve. The calcination can be carried out in any conventional manner known in the art, such as a calcination temperature of generally 300-800°C, preferably 400-650°C, and a calcination time of generally 1-10 hours, preferably 3-6 hours. In addition, the calcination is generally carried out in an oxygen-containing atmosphere, such as air or oxygen atmosphere.
[0058] In a third aspect, the present invention provides a molecular sieve composition, which comprises the IWV / MFI co-crystallized molecular sieve described in the first aspect of the present invention, and a binder.
[0059] The IWV / MFI co-crystallized molecular sieve of the present invention can be used in combination with other materials to obtain a molecular sieve composition. Examples of the other materials include active materials such as synthetic zeolites and natural zeolites, and inactive materials (generally referred to as binders) such as clay, clay, silica gel, alumina, silicon oxide and magnesium oxide. These other materials can be used alone or in combination in any proportion. The amount of the other materials can be directly referred to the conventional amount in the art, without any particular limitation.
[0060] In a fourth aspect, the present invention provides use of the IWV / MFI co-crystallized molecular sieve described in the first aspect or the molecular sieve composition described in the third aspect of the present invention in catalytic reaction, adsorption or ion exchange.
[0061] The IWV / MFI co-crystallized molecular sieve or the molecular sieve composition containing the IWV / MFI co-crystallized molecular sieve of the present invention can be used as an adsorbent, for example, to separate at least one component from a mixture of multiple components in a gas phase or a liquid phase. Accordingly, the at least one component can be partially or substantially completely separated from a mixture of various components, for example, by contacting the mixture with the IWV / MFI co-crystallized molecular sieve or the molecular sieve composition containing the IWV / MFI co-crystallized molecular sieve, and selectively adsorbing this component. In addition, the IWV / MFI co-crystallized molecular sieve or the molecular sieve composition containing the IWV / MFI co-crystallized molecular sieve of the present invention can also be used as a catalyst, especially a catalyst in an organic compound conversion reaction.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] 1. The IWV / MFI co-crystallized molecular sieve of the present invention has two physical phases, namely, the IWV molecular sieve and the MFI molecular sieve. Compared with the molecular sieve of a single crystal form, it has more catalytic active sites and better adsorption performance.
[0064] 2. The IWV / MFI co-crystallized molecular sieve of the present invention contains silicon, germanium and trivalent framework elements. The various framework elements can further increase the catalytic and adsorption active sites and improve the catalytic and adsorption performance of the molecular sieve.
[0065] 3. The present invention can realize the preparation of IWV / MFI co-crystallized molecular sieve using a single template, and the ratio of the two phases in the co-crystallization is adjustable, which can meet different usage requirements, has a simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] The accompanying drawings are used to provide further understanding of the present application and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present application, but do not constitute a limitation to the present application.
[0067] Figure 1 This is the XRD spectrum of the IWV / MFI co-crystallized molecular sieve prepared in Example 1.
[0068] Figure 2 This is a SEM image of the IWV / MFI co-crystallized molecular sieve prepared in Example 1.
[0069] Figure 3 This is the XRD spectrum of the IWV / MFI co-crystallized molecular sieve prepared in Example 2.
[0070] Figure 4 This is the SEM image of the IWV / MFI co-crystallized molecular sieve prepared in Example 2. DETAILED DESCRIPTION
[0071] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.
[0072] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0073] In this paper, the structure of the molecular sieve is determined by an X-ray diffraction spectrum (XRD), which is measured by an X-ray powder diffractometer using a Cu-Kα ray source with a Kα1 wavelength of λ = 1.5405980 angstroms. Nickel filter.
[0074] In the present invention, an X'Pert PRO X-ray powder diffraction (XRD) instrument of PANalytical Company of the Netherlands is used, with an operating voltage of 40 kV, a current of 40 mA, and a scanning range of 5 to 40°.
[0075] In the present invention, the scanning electron microscope (SEM) images were obtained by a Japanese HITACHI S4800 field emission scanning electron microscope, and the test conditions were as follows: voltage 3 kV, current 50 mA.
[0076] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.
[0077] In the present invention, the “C 1-6 " means the number of carbon atoms is 1-6, for example, the number of carbon atoms is 1, 2, 3, 4, 5 or 6; "C 1-6 The term "alkyl" refers to an alkyl group having 1 to 6 carbon atoms, including but not limited to methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, isopentyl, cyclopentyl, hexyl, isohexyl, cyclohexyl, and the like.
[0078] Unless otherwise specified, the reagents used in the following examples of the present invention can be obtained through commercial channels.
[0079] Example 1
[0080] Dissolve 0.929g of germanium oxide and 0.136g of aluminum isopropoxide in 15.82g of 1,1,3,5-TMPOH aqueous solution (20wt%), slowly add 6.473g of tetraethyl orthosilicate (TEOS), stir at room temperature, and after hydrolysis is complete, open the container and stir overnight to evaporate ethanol, isopropanol and part of the water, add 1g of hydrofluoric acid (40wt%), stir evenly and adjust the amount of water until the reaction mixture reaches the following molar composition:
[0081] 0.5(1,1,3,5-TMPOH):0.778SiO2:0.222GeO2:0.00833Al2O3:0.5HF:17.5H2O
[0082] The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 175°C oven for crystallization for 264 hours. The solid after the reaction was filtered, washed with distilled water, and dried at 100°C to obtain a raw powder solid, which was placed in a muffle furnace and calcined at 550°C for 5 hours to obtain the final product.
[0083] The XRD pattern of the final product is as follows: Figure 1 As shown in the SEM images Figure 2 As shown. Figure 1 It can be seen that the product is an IWV / MFI co-crystallized molecular sieve, in which the weight percentage of the IWV molecular sieve is 45%. The spectrum data is shown in Table 2. Figure 2 It can be seen that the product contains both IWV molecular sieve flake crystals and MFI molecular sieve block crystals. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 6.
[0084] Table 2
[0085]
[0086]
[0087] Example 2
[0088] Dissolve 0.762g of germanium oxide and 0.163g of aluminum isopropoxide in 23.73g of 1,1,3,5-TMPOH aqueous solution (20wt%), slowly add 6.806g of tetraethyl orthosilicate (TEOS), stir at room temperature, and after complete hydrolysis, open the container and stir overnight to evaporate ethanol, isopropanol and part of the water, add 1.5g of hydrofluoric acid (40wt%), stir evenly and adjust the amount of water until the reaction mixture reaches the following molar composition:
[0089] 0.75(1,1,3,5-TMPOH):0.818SiO2:0.182GeO2:0.01Al2O3:0.75HF:20H2O
[0090] The mixture was placed in a crystallization kettle lined with polytetrafluoroethylene and placed in an oven at 175°C for crystallization for 288 hours. The solid after the reaction was filtered, washed, dried and calcined to obtain the final product.
[0091] The XRD pattern of the final product is as follows: Figure 3 As shown in the SEM photos Figure 4 As shown. Figure 3 It can be seen that the product is an IWV / MFI co-crystallized molecular sieve, in which the weight percentage of the IWV molecular sieve is 60%. The spectrum data is shown in Table 3. Figure 4 It can be seen that the product contains both IWV molecular sieve flake crystals and MFI molecular sieve block crystals. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 6.
[0092] Table 3
[0093]
[0094] Example 3
[0095] 0.644g of germanium oxide and 0.065g of pseudo-boehmite (containing 70wt% Al2O3) were dissolved in 31.64g of 1,1,3,5-TMPOH aqueous solution (20wt%), 7.039g of tetraethyl orthosilicate (TEOS) was slowly added, and stirred at room temperature. After the hydrolysis was complete, the container was opened and stirred overnight to evaporate ethanol and part of the water, and 5g of ammonium fluoride solution (37wt%) was added. After stirring evenly, the amount of water was adjusted until the reaction mixture reached the following molar composition:
[0096] 1.0(1,1,3,5-TMPOH):0.846SiO2:0.154GeO2:0.0111Al2O3:1.25NH4F:16H2O
[0097] The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 170°C oven for crystallization for 312 hours. The solid after the reaction was filtered, washed, dried, and calcined to obtain the final IWV / MFI co-crystallized molecular sieve, wherein the weight percentage of the IWV molecular sieve was 70%, and the XRD spectrum was similar to that of the Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 6.
[0098] Example 4
[0099] 0.494g of germanium oxide and 0.149g of aluminum isopropoxide were dissolved in 25.31g of 1,1,3,5-TMPOH aqueous solution (20wt%), 2.646g of silica sol (Ludox HS-40, containing 40wt% SiO2) and 1.114g of white carbon black (containing 95wt% SiO2) were slowly added, and stirred at room temperature. The container was left open and stirred overnight to evaporate the isopropanol and part of the water, and 1.6g of hydrofluoric acid (40wt%) and 1.6g of ammonium fluoride solution (37wt%) were added. After stirring evenly, the amount of water was adjusted until the reaction mixture reached the following molar composition:
[0100] 0.8(1,1,3,5-TMPOH):0.882SiO2:0.118GeO2:0.0091Al2O3:0.8HF:0.4NH4F:18H2O
[0101] The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 160°C oven for crystallization for 360 hours. The solid after the reaction was filtered, washed, dried, and calcined to obtain the final IWV / MFI co-crystallized molecular sieve, wherein the weight percentage of the IWV molecular sieve was 80%, and the XRD spectrum was similar to that of the Figure 1 Similarly, the composition of the raw materials for synthesizing the molecular sieve is shown in Table 6.
[0102] Example 5
[0103] Dissolve 0.837g germanium oxide and 0.19g aluminum sulfate 18hydrate in 18.98g 1,1,3,5-TMPOH aqueous solution (20wt%), slowly add 2.021g white carbon black (containing 95wt% SiO2), stir at room temperature, leave the container open and stir overnight to evaporate part of the water, add 1.6g hydrofluoric acid (40wt%), stir evenly and adjust the amount of water until the reaction mixture reaches the following molar composition:
[0104] 0.6(1,1,3,5-TMPOH):0.8SiO2:0.2GeO2:0.00714Al2O3:0.8HF:25H2O
[0105] The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 165°C oven for crystallization for 336 hours. The solid after the reaction was filtered, washed, dried and calcined to obtain the final IWV / MFI co-crystallized molecular sieve product, wherein the weight percentage of the IWV molecular sieve was 25%. The XRD spectrum data is shown in Table 4. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 6.
[0106] Table 4
[0107]
[0108]
[0109] Example 6
[0110] 0.598g of germanium oxide, 0.115g of aluminum isopropoxide, and 0.04g of pseudo-boehmite (containing 70wt% Al2O3) were dissolved in 38g of 1,1,3,5-TMPOH aqueous solution (20wt%), and 7.13g of tetraethyl orthosilicate (TEOS) was slowly added, and stirred at room temperature. After the hydrolysis was complete, the container was opened and stirred overnight to evaporate ethanol, isopropanol and part of the water, and 1g of hydrofluoric acid (40wt%) and 2g of ammonium fluoride solution (37wt%) were added. After stirring evenly, the amount of water was adjusted until the reaction mixture reached the following molar composition:
[0111] 1.2(1,1,3,5-TMPOH):0.857SiO2:0.143GeO2:0.0139Al2O3:0.5HF:0.5NH4F:28H2O
[0112] The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in an oven at 180°C for crystallization for 240 hours. The solid after the reaction was filtered, washed, dried and calcined to obtain the final IWV / MFI co-crystallized molecular sieve product, wherein the weight percentage of IWV molecular sieve was 85%, and the XRD spectrum was consistent with Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 6.
[0113] Example 7
[0114] 929g of germanium oxide and 0.136g of aluminum isopropoxide were dissolved in 15.82g of 1,1,3,5-TMPOH aqueous solution (20wt%), 6.307g of tetraethyl orthosilicate (TEOS) and 0.277g of tetrabutyl titanate (TBOT) were slowly added, and the mixture was stirred at room temperature. After the hydrolysis was complete, the container was opened and stirred overnight to evaporate ethanol, isopropanol, butanol and part of the water, and 1g of hydrofluoric acid (40wt%) was added. After stirring evenly, the amount of water was adjusted until the reaction mixture reached the following molar composition:
[0115] 0.5(1,1,3,5-TMPOH):0.758SiO2:0.222GeO2:0.02TiO2:0.00833Al2O3:0.5HF:16.7H2O
[0116] The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 175°C oven for crystallization for 264 hours. The solid after the reaction was filtered, washed, dried and calcined to obtain the final IWV / MFI co-crystallized molecular sieve product, wherein the weight percentage of the IWV molecular sieve was 50%. The XRD spectrum data are shown in Table 5. The raw material composition for synthesizing the molecular sieve is shown in Table 6.
[0117] Table 5
[0118]
[0119] Example 8
[0120] 0.929g germanium oxide, 0.123g aluminum isopropoxide, 0.004g boric acid were dissolved in 15.82g 1,1,3,5-TMPOH aqueous solution (20wt%), 6.473g tetraethyl orthosilicate (TEOS) were slowly added, and stirred at room temperature. After the hydrolysis was complete, the container was opened and stirred overnight to volatilize ethanol, isopropanol and part of the water, 1g hydrofluoric acid (40wt%) was added, and the amount of water was adjusted after stirring evenly until the reaction mixture reached the following molar composition:
[0121] 0.5(1,1,3,5-TMPOH):0.778SiO2:0.222GeO2:0.0075Al2O3:0.00083B2O3:0.5HF:18H2O
[0122] The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 170°C oven for crystallization for 300 hours. The solid after the reaction was filtered, washed, dried, and calcined to obtain the final IWV / MFI co-crystallized molecular sieve product, wherein the weight percentage of IWV molecular sieve was 40%, and the XRD spectrum was similar to that of Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 6.
[0123] Example 9
[0124] 0.929g germanium oxide, 0.102g aluminum isopropoxide, 0.01g boric acid were dissolved in 15.82g 1,1,3,5-TMPOH aqueous solution (20wt%), 6.473g tetraethyl orthosilicate (TEOS) were slowly added, and stirred at room temperature. After the hydrolysis was complete, the container was opened and stirred overnight to volatilize ethanol, isopropanol and part of the water, 1g hydrofluoric acid (40wt%) was added, and the amount of water was adjusted after stirring evenly until the reaction mixture reached the following molar composition:
[0125] 0.5(1,1,3,5-TMPOH):0.778SiO2:0.222GeO2:0.00623Al2O3:0.0021B2O3:0.5HF:21H2O
[0126] The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 175°C oven for crystallization for 336 hours. The solid after the reaction was filtered, washed, dried, and calcined to obtain the final IWV / MFI co-crystallized molecular sieve product, wherein the weight percentage of IWV molecular sieve was 35%, and the XRD spectrum was similar to that of Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 6.
[0127] Example 10
[0128] 0.929 g of germanium oxide, 0.123 g of aluminum isopropoxide, and 0.004 g of boric acid were dissolved in 15.82 g of 1,1,3,5-TMPOH aqueous solution (20 wt%), 6.307 g of tetraethyl orthosilicate (TEOS) and 0.277 g of tetrabutyl titanate (TBOT) were slowly added, and the mixture was stirred at room temperature. After the hydrolysis was complete, the container was opened and stirred overnight to evaporate ethanol, isopropanol, butanol and part of the water, 1 g of hydrofluoric acid (40 wt%) was added, and the amount of water was adjusted after stirring evenly until the reaction mixture reached the following molar composition: 0.5 (1,1,3,5-TMPOH): 0.758 SiO2: 0.222 GeO2: 0.02 TiO2: 0.0075 Al2O3: 0.00083 B2O3: 0.5 HF: 18.1 H2O
[0129] The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in an oven at 185°C for crystallization for 216 hours. The solid after the reaction was filtered, washed, dried and calcined to obtain the final IWV / MFI co-crystallized molecular sieve product, wherein the weight percentage of IWV molecular sieve was 30%, and the XRD spectrum was similar to that of Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 6.
[0130] Table 6 Molecular sieve raw material composition (molar ratio) of Examples 1-10
[0131]
[0132] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An IWV / MFI co-crystallized molecular sieve having a chemical composition of m SiO2·n GeO2·x XO 1.5 , in, X is a skeleton trivalent element, the molar ratio of SiO2 to GeO2 is m:n=(2.5-10):1, and the sum of the molar numbers of SiO2 and GeO2 is equal to XO 1.5 The molar ratio (m+n): x=(35-80):
1.
2. The cocrystallized molecular sieve according to claim 1, characterized in that: m:n=(3-8):1; and / or, (m+n): x=(40-60): 1; and / or, m+n=1; and / or, X is selected from at least one of Group IIIA elements, Group VIII elements, Group VIB elements or Group IIIB elements, preferably at least one of aluminum, boron, iron, gallium, indium and chromium, more preferably aluminum and / or boron; Optionally, Si in the co-crystallized molecular sieve is replaced by at least one non-silicon tetravalent skeleton element Y, preferably, element Y is selected from at least one of tin, titanium, zirconium and hafnium; preferably, no more than 10wt% of the Si element in the molecular sieve is replaced by element Y.
3. The cocrystallized molecular sieve according to claim 1 or 2, characterized in that: The X-ray diffraction pattern of the co-crystallized molecular sieve includes the following characteristic peaks:
4. The cocrystallized molecular sieve according to any one of claims 1 to 3, characterized in that The co-crystallized molecular sieve has two phases: IWV molecular sieve and MFI molecular sieve; Preferably, based on the total weight of the co-crystallized molecular sieve, the content of the IWV molecular sieve is 1wt%-99wt%, preferably 5wt%-95wt%, and the content of the MFI molecular sieve is 1wt%-99wt%, preferably 5wt%-95wt%; Preferably, the IWV molecular sieve is in the form of flakes, and the MFI molecular sieve is in the form of blocks.
5. The method for preparing the IWV / MFI cocrystallized molecular sieve according to any one of claims 1 to 4, comprising the following steps: A mixed solution containing a silicon source, a germanium source, an optional non-silicon tetravalent framework element Y source, a trivalent framework element X source, a fluorine source, a structure directing agent R and water is subjected to a crystallization reaction to obtain an IWV / MFI co-crystallized molecular sieve.
6. The preparation method according to claim 5, characterized in that: The silicon source is calculated as SiO2, the germanium source is calculated as GeO2, the non-silicon tetravalent skeleton element Y source is calculated as oxide YO2, the trivalent skeleton element X source is calculated as oxide X2O3, and the fluorine source is calculated as F. In the mixed solution, the molar ratio of SiO2 to GeO2 is (2.5-10):1, preferably (3-8):1; and / or, The molar ratio of YO2 to SiO2 is (0-0.1):1, preferably (0.01-0.09):1; and / or, The ratio of the sum of the molar numbers of SiO2 and GeO2 to the molar number of X2O3 is (70-160):1, preferably (80-120):1; and / or, The molar ratio of the sum of the molar numbers of SiO2 and GeO2 to F is 1:(0.2-4), preferably (0.35-2.5):1; and / or, The molar ratio of the sum of the moles of SiO2 and GeO2 to the structure directing agent R is 1:(0.15-4), preferably 1:(0.35-2); Preferably, in the mixed solution, the molar ratio of structure directing agent R, SiO2, GeO2, X2O3, F and water is (0.15-4):(0.714-0.909):(0.091-0.286):(0.00625-0.0143):(0.2-4):(12-40).
7. The preparation method according to claim 5 or 6, characterized in that: The silicon source is selected from at least one of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieve and tetraalkoxysilane; And / or, the germanium source is selected from at least one of germanium oxide, germanium nitrate and tetraalkoxygermanium; And / or, the non-silicon tetravalent skeleton element Y source is selected from at least one of a tin source, a titanium source, a zirconium source and a hafnium source; preferably, the tin source is selected from at least one of tin tetrachloride, stannous chloride, alkyl tin, alkoxy tin and organic tin esters, the titanium source is selected from at least one of tetraalkyl titanates such as tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetra-n-butyl titanate, titanium tetrachloride, hexafluorotitanic acid, titanium sulfate and their hydrolyzates, the zirconium source is selected from at least one of zirconium nitrate, zirconium tetrachloride, zirconium oxide and alkoxy zirconium; the hafnium source is selected from at least one of hafnium oxide and hafnium sulfate; And / or, the trivalent skeleton element X source is selected from at least one of an aluminum source, a boron source, an iron source, a gallium source, an indium source and a chromium source. Preferably, the aluminum source is selected from at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum chloride, pseudo-boehmite, aluminum oxide, aluminum hydroxide, silica-aluminum zeolite molecular sieve, aluminum carbonate, elemental aluminum, aluminum isopropoxide and aluminum acetate; the boron source is selected from at least one of boric acid, sodium tetraborate, amorphous boron oxide, potassium borate, sodium metaborate, ammonium tetraborate and organic boron esters; the iron source is selected from at least one of iron sulfate, iron nitrate, iron halide such as ferric chloride, ferrocene and ferric citrate; the gallium source is selected from at least one of gallium oxide and gallium nitrate; the indium source is selected from at least one of indium oxide and indium nitrate; the chromium source is selected from at least one of chromium oxide, chromium chloride and chromium nitrate; And / or, the fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The structure directing agent R is selected from a compound containing 1,1,3,5-tetraalkylpiperidinium ions or a compound having a structure shown in formula I, In Formula I, R1 to R4 are each independently selected from H and C 1-6 alkyl, preferably hydrogen, methyl, ethyl, propyl, isopropyl, butyl, isobutyl and tert-butyl; Preferably, the anion X in the structure directing agent - Selected from halogen ions and hydroxide ions, preferably Cl - Br - ,I - and OH - , more preferably OH - ; Preferably, the structure directing agent R is 1,1,3,5-tetramethylpiperidinium hydroxide; and / or, the temperature of the crystallization reaction is 100-200° C., preferably 155-175° C.; and / or, the time of the crystallization reaction is 72-600 hours, preferably 120-360 hours; And / or, the method further comprises: performing post-treatment after the crystallization reaction, wherein the post-treatment comprises the steps of filtering, washing, drying and optional calcination.
9. A molecular sieve composition, comprising the co-crystallized molecular sieve according to any one of claims 1 to 4, and a binder; preferably, the binder is selected from at least one of clay, kaolin, silica gel, alumina, silicon oxide and magnesium oxide.
10. Use of the IWV / MFI co-crystallized molecular sieve according to any one of claims 1 to 4 or the molecular sieve composition according to claim 9 in catalytic reaction, adsorption or ion exchange.
